2017
DOI: 10.1002/lary.26517
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of patients who underwent aesthetic rhinoplasty: 100 cases assessed with the Glascow Benefit Inventory

Abstract: 2c Laryngoscope, 127:2017-2025, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The lack of difference between the two groups in quality of life might be due to the small sample size and utilization of the convenience sampling method in the current study. The results of the present study, however, are in line with those of the study by Kotzampasakis et al ., indicating a significant increase in quality of life after rhinoplasty,[ 18 ] however, inconsistent with the results of the study by Yang et al ., reporting evident improvement in the quality of life after rhinoplasty in all the studied patients;[ 19 ] Cultural differences in the two communities studied (our study and those cited) as well as the lack of quality of life after rhinoplasty may be the main reasons for these differences.…”
Section: Discussionmentioning
confidence: 64%
“…The lack of difference between the two groups in quality of life might be due to the small sample size and utilization of the convenience sampling method in the current study. The results of the present study, however, are in line with those of the study by Kotzampasakis et al ., indicating a significant increase in quality of life after rhinoplasty,[ 18 ] however, inconsistent with the results of the study by Yang et al ., reporting evident improvement in the quality of life after rhinoplasty in all the studied patients;[ 19 ] Cultural differences in the two communities studied (our study and those cited) as well as the lack of quality of life after rhinoplasty may be the main reasons for these differences.…”
Section: Discussionmentioning
confidence: 64%
“…Interestingly, the findings of our study, which detected an increase in EQ-5D VAS score larger than 9.5 in the cohort of all patients included in the study, in the group of patients with NAO before surgery, and in the group of patients with septal correction but not in the groups of patients in which the increase of EQ-5D VAS after surgery was not significant (►Table 1), corroborate the MCID of the EQ-5D VAS score as defined by Fuller et al 11 An improvement of generic HRQoL after rhinoplasty was also demonstrated by studies using EQ-5D VAS, 12 World Health Organization Quality-of-Life Scale (WHOQOL) 13,14 and Glasgow Benefit Inventory (GBI). [15][16][17][18] Contrary to the findings of these studies, Zojaji et al used General Health Questionnaire and WHOQOL to assess changes after aesthetic rhinoplasty and could find no improvement in HRQoL except for the psychologic-related health domains. 19 Studying long-term changes of generic HRQoL after septorhinoplasty, Bulut et al found an improvement in six SF-36 domains: physical functioning, physical limitation, pain, energy, social functioning and well-being, but not on general Abbreviations: CI, confidence interval; SD, standard deviation.…”
Section: Discussionmentioning
confidence: 97%
“…10 If BDD and other psychopathology are ruled out, the patient can then be counseled regarding surgery; however, if the surgeon still has significant concerns it may be necessary to get a second opinion. [15][16][17][18][19][20] Cosmetic procedures screening scale 21 Derriford appearance scale (DAS59) 18,22,23 Expectations of esthetic rhinoplasty scale (EARS) 24 Body dysmorphic disorder questionnaire (BDDQ) 25 Brief fear of negative evaluation scale 25 The Utrecht questionnaire for outcome assessment in esthetic rhinoplasty 26 Yale-Brown obsessive scale modified for BDD 22 Hospital anxiety and depression scale 26 The RHINO scale 27 Dysmorphic concern questionnaire 28 Glasgow benefit inventory 23,[29][30][31][32][33] FACE-Q 20,[34][35][36][37][38][39] Neuroticism-extraversion-openness fivefactor inventory (NEO-FFI) 40 Body dysmorphic disorder examinationself report (BDDE-SR) 41 Symptom checklist-90-revised (SCL-90-R) 40 Determining preoperative expectations is crucial as poor outcomes are more frequently due to emotional dissatisfaction rather than technical failure. 42,43 The use of the rhinoplasty improvement scale is helpful in counseling patients about realistic postsurgical expectations; moving up one point on the scale is realistic but anything more than this is unlikely (Fig.…”
Section: Ijhnsmentioning
confidence: 99%